2018
DOI: 10.1159/000489803
|View full text |Cite
|
Sign up to set email alerts
|

MiR-598 Suppresses Invasion and Migration by Negative Regulation of Derlin-1 and Epithelial-Mesenchymal Transition in Non-Small Cell Lung Cancer

Abstract: Background/Aims: MicroRNAs regulate a wide range of biological processes of non-small cell lung cancer (NSCLC). Although miR-598 has been reported to act as a suppressor in osteosarcoma and colorectal cancer, the physiological function of miR-598 in NSCLC remains unknown. In this study, the role of miR-598 in NSCLC was investigated. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to estimate the expression of miR-598 and Derlin-1 (DERL1) in both NSCLC tissues and cell lines. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…This finding is in total agreement with an early report on the consistent detection of Vimentin expression in six cell lines explanted from COMM (including Shadow), a skin melanoma‐derived cell line and 28/29 tumour sections prepared from 11 COMM, 14 cutaneous and 4 digital canine melanomas . Vimentin is generally expressed by mesenchymal and neuroectodermal cells in normal tissue, and neoplastic cells that had undergone EMT in a high proportion of canine cancers . Along with Vimentin, tumour sections and primary cell lines consistently expressed biologically active MMP2 as revealed by IF and zymography.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in total agreement with an early report on the consistent detection of Vimentin expression in six cell lines explanted from COMM (including Shadow), a skin melanoma‐derived cell line and 28/29 tumour sections prepared from 11 COMM, 14 cutaneous and 4 digital canine melanomas . Vimentin is generally expressed by mesenchymal and neuroectodermal cells in normal tissue, and neoplastic cells that had undergone EMT in a high proportion of canine cancers . Along with Vimentin, tumour sections and primary cell lines consistently expressed biologically active MMP2 as revealed by IF and zymography.…”
Section: Discussionsupporting
confidence: 92%
“…16 Inhibition of NSCLC cells growth and metastasis has been recognized as an effective treating strategy for NSCLC. Previous studies have demonstrated that a growing number of miRNAs played a role in the limiting tumor growth and EMT process in NSCLC, such as miR-206, 18 miR-598, 19 miR-126, 20 and miR-185. 17 EMT contributes a lot to tumor metastasis by changing tumor cells shape and improving the migratory and invasive capacities of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…17 EMT contributes a lot to tumor metastasis by changing tumor cells shape and improving the migratory and invasive capacities of tumor cells. Previous studies have demonstrated that a growing number of miRNAs played a role in the limiting tumor growth and EMT process in NSCLC, such as miR-206, 18 miR-598, 19 miR-126, 20 and miR-185. 21 However, we for the first time, suggested that miR-105 was also one of the key regulators in modulating NSCLC cells EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Using CCK-8 and Transwell assays, it was revealed that miR-671-3p inhibited NSCLC cell proliferation and invasion. miRNAs have been demonstrated to target mRNAs for the regulation of gene expression in cancer (23). Through bioinformatics analysis, the present study identified that miR-671-3p may target CCND2.…”
Section: Discussionmentioning
confidence: 74%